2008
DOI: 10.1038/ncprheum0677
|View full text |Cite
|
Sign up to set email alerts
|

A case of Erdheim–Chester disease initially mistaken for Ormond's disease

Abstract: Treatment with glucocorticoids failed. The patient's symptoms improved significantly after initiation of interferon-alpha therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…We investigated whether it was inducible in vivo by monitoring Siglec-1 expression before and during therapy with IFN␣2a in a patient newly diagnosed as having Erdheim-Chester disease (43). The patient received IFN␣2a (3 ϫ 10 6 IU) subcutaneously 3 times per week.…”
Section: Resultsmentioning
confidence: 99%
“…We investigated whether it was inducible in vivo by monitoring Siglec-1 expression before and during therapy with IFN␣2a in a patient newly diagnosed as having Erdheim-Chester disease (43). The patient received IFN␣2a (3 ϫ 10 6 IU) subcutaneously 3 times per week.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of drugs have been used like steroids, cyclophosphamide, vinblastine, vincristine, adriamycin, colchicine and interferon-1α with different clinical responses [4, 6, 7, 13, 15, 16]. In our case, the first choice of treatment was pulsed steroids as there are reports of partial response [5, 6], but we found no improvement.…”
Section: Discussionmentioning
confidence: 62%
“…Our review of the literature, including this case, identified 6 more patients with ECD and definite pulmonary involvement [5,6,7,8,9], of whom 3 had a poor outcome, highlighting its aggressive nature once the lungs are involved. Other recent cases with multisystemic involvement had variable outcomes [10,11,12,13,14,15], and a review of the literature suggests 250 published reports [14]. It is also interesting to note the cardiac involvement which, although not as well described as pulmonary involvement, may be an additional adverse prognostic indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic reports have described glucocorticoids, cyclophosphamide, vincristine, adriamycin, colchicine and radiotherapy as effective against ECD due to the low frequency of this disorder [6,7,11,12,13]. In our patient, the first-choice treatment was systemic corticosteroids.…”
Section: Discussionmentioning
confidence: 78%